Evaluation of Monthly and Annual Mean Concentrations of Air Pollutants in Tehran Metropolis (Tehran Air Pollution Control Bureau's Air Pollution Measurement Stations in 2012-2012) - Mohammad Rastgari; Elmira Mousazadeh Namini; Nasrin Hashemi Tonekaboni (محیط زیست و توسعه فرابخشی, 2020)
Removing environmental pollution has become one of the main concerns of mankind today. Air quality in cities depends on the weather and the amount of pollutants produced. Today, air pollution is one of the most complex problems in human societies, which has had many negative effects on the health of living things, especially humans. In this study, the average monthly and annual concentrations of air pollutants in the air pollution measuring stations of Tehran Environmental Protection Bureau were evaluated in 91 to 97 years.The results showed that the highest concentration of major pollutants in Tehran in 1997 had a relatively decreasing trend compared to the previous year. Comparative statistics of the mean annual concentration of indicator pollutants show that CO levels in all stations decreased in 97 at most stations and O3 at all stations compared to the previous year, (it should be explained that the ozone pollutant at Shofuf station in 1997 to the geophysical station has been transferred). The average concentration of NO2, SO2, PM10 and PM2.5 pollutants in air pollution measuring stations and comparing it with the (WHO) standard indicates that all stations are in poor condition and above the standard level.